2017
DOI: 10.1111/jcmm.13138
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of adipose‐derived stem cells from subcutaneous and visceral fat as a potential cell source for knee osteoarthritis treatment

Abstract: The intra‐articular injection of adipose‐derived stem cells (ASCs) is a novel potential therapy for patients with osteoarthritis (OA). However, the efficacy of ASCs from different regions of the body remains unknown. This study investigated whether ASCs from subcutaneous or visceral adipose tissue provide the same improvement of OA. Mouse and human subcutaneous and visceral adipose tissue were excised for ASC isolation. Morphology, proliferation, surface markers and adipocyte differentiation of subcutaneous AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 30 publications
2
38
2
Order By: Relevance
“…Whether this relates to bona fide differences in therapeutic efficacy between MSCs derived from different tissues is unclear. MSCs are defined by the characteristics of self-renewal and multi-potent differentiation; however, cells from different strains of mice [43], different tissues [44], and tissue sites [45] within mice, and even subpopulations within a single tissue [46], show variability in their differentiation potential and associated cell-surface markers. The multi-potent MSCs used in the current study had poorer adipogenic compared with their osteo-and chondro-genic ability, and despite being~90% positive for the MSC marker Sca-1 (similar to previous OAtherapeutic studies using MSCs from bone marrow [43] or adipose tissue [23,24]), they had only modest CD29 expression and were negative for CD105.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this relates to bona fide differences in therapeutic efficacy between MSCs derived from different tissues is unclear. MSCs are defined by the characteristics of self-renewal and multi-potent differentiation; however, cells from different strains of mice [43], different tissues [44], and tissue sites [45] within mice, and even subpopulations within a single tissue [46], show variability in their differentiation potential and associated cell-surface markers. The multi-potent MSCs used in the current study had poorer adipogenic compared with their osteo-and chondro-genic ability, and despite being~90% positive for the MSC marker Sca-1 (similar to previous OAtherapeutic studies using MSCs from bone marrow [43] or adipose tissue [23,24]), they had only modest CD29 expression and were negative for CD105.…”
Section: Discussionmentioning
confidence: 99%
“…ADSCs also had positive effects on knee joint quality. Intra‐articular injections with these cells were shown to slow the progression of knee OA by limiting joint damage and cartilage degeneration . Li et al found that ADSC treatment showed significantly higher scores or better tissue preservation using a modified O'Driscoll histologic score when compared to the control group .…”
Section: Resultsmentioning
confidence: 99%
“…This stress impacts on ASC mitochondria leading to DNA damage, telomere shortening, reduced proliferation and stemness (as evidenced by decreased expression of NANOG, SOX2 and OCT4), increased apoptosis and senescence [101]. Interestingly, differences are emerging in the performance of ASCs isolated from either subcutaneous or visceral fat and from different anatomical sites [102] or as a function of the metabolic status of the subject, with particular reference to obesity. White adipose tissue deregulation is pivotal in metabolic syndrome.…”
Section: In Vivo Msc Senescencementioning
confidence: 99%